Levels of biogenic amines in lung tissues of patients with non-small cell lung cancer after COVID-19 of various severity - O. I. Kit; E. M. Frantsiyants; D. A. Kharagezov; V. A. Bandovkina; Yu. A. Pogorelova; N. D. Cheryarina; Yu. N. Lazutin; A. G. Milakin; I. A. Leyman; O. N. Stateshny; N. D. Ushakova (Южно-Российский онкологический журнал)
Purpose of the study. Was to analyze levels of biogenic amines (serotonin and its metabolite 5-HIAA, dopamine, norepinephrine and histamine) in lung tissues of patients with lung cancer with previous COVID-19 infection.Patients and methods. The study was carried out on samples of intact lung tissues, tumor tissues and peritumoral lung tissues obtained during open biopsy while performing radical surgery from patients with morphologically verified non-small cell lung cancer (NSCLC), stage I–IIIA (cT1–3NХM0). The main group included 30 NSCLC patients (15 men and 15 women) after severe or moderate to severe COVID-19 who required hospitalization. The control group included 15 men and 15 women with NSCLC after asymptomatic or mild SARS-CoV-2 infection. The mean age of patients was 59.11 ± 2.9 years. Levels of dopamine, norepinephrine, serotonin, 5-hydroxyindoleacetic acid (5-HIAA) and histamine were measured by ELISA (IBL, Germany).Results. All studied lung tissue samples from men and women of the main group, compared to the control group, showed deficiency of catecholamines with their ratio unchanged, and changes in serotonin metabolism to ensure its stable level. Thus, levels of dopamine in samples of patients of the main group were lower on average by 1.3 times, norepinephrine by 1.3–3.3 times, serotonin by 1.6 times, and 5-HIAA by 1.8–4 times. At the same time, sex differences were observed in histamine levels. Regardless of the COVID-19 severity, levels of diamine in women were lower in the resection line tissue by an average of 2.4 times, and in the peritumoral tissue by 1.6 times, compared with men, but there were no sex differences in the tumor tissue. Conclusion. Apparently, changes in the levels of dopamine, norepinephrine, and serotonin in lung tissues could be associated with the severity of SARS-CoV-2 infection. Since dopamine is involved in counteracting the carcinogenic action of the adrenergic system and in the regulation of various immunocompetent cells in the tumor microenvironment, such changes in the biogenic status in the lungs of patients of the main group could lead to a more severe tumor course.